2008
DOI: 10.1159/000151315
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic position of the saola <i>(Pseudoryx nghetinhensis)</i> inferred from cytogenetic analysis of eleven species of Bovidae

Abstract: Previous morphological and molecular analyses failed to resolve the phylogenetic position of the critically endangered saola (Pseudoryx nghetinhensis) with respect to its placement in Bovina (cattle, bison, and yak) or Bubalina (Asian and African buffaloes). In the present study, G- and C-banding, Ag-staining and FISH with 28S and telomeric probes was undertaken for 17 bovid species. An analysis of these data allowed us to identify 49 structural rearrangements that included autosomes, gonosomes and 17 differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 92 publications
3
24
0
Order By: Relevance
“…The A cytotype has retained the Caprini type. Three structural variants of the X chromosome were detected among bovids according to studies supporting previous findings [see for example Robinson et al, 1997Robinson et al, , 1998Gallagher et al, 1999;Rubes et al, 2007;Nguyen et al, 2008]. The intrachromosomal rearrangements which differentiated the X chromosomes of the Bovinae from the Caprinae were described by Iannuzzi et al [2000] using comparative FISH mapping with 17 markers.…”
supporting
confidence: 74%
“…The A cytotype has retained the Caprini type. Three structural variants of the X chromosome were detected among bovids according to studies supporting previous findings [see for example Robinson et al, 1997Robinson et al, , 1998Gallagher et al, 1999;Rubes et al, 2007;Nguyen et al, 2008]. The intrachromosomal rearrangements which differentiated the X chromosomes of the Bovinae from the Caprinae were described by Iannuzzi et al [2000] using comparative FISH mapping with 17 markers.…”
supporting
confidence: 74%
“…At present, we still do not know whether these variations in number and position of the NORs offer any selective advantage to the species; however, they seem to evolve independently of the centric fusions and may represent a useful source of information for studying evolutionary relationships among species, as suggested by Gallagher et al [1999] and demonstrated recently by Nguyen et al [2008].…”
Section: A B Cmentioning
confidence: 96%
“…In phylogenetic reconstructions, such results have sometimes been interpreted as a signature of homoplasy, when in fact they may correspond to hemiplasy or lineage sorting (Robinson et al, 2008). An illustration of this may be found in a recent phylogenetic analysis of Bovidae using chromosomal characters, 17 of which were NORs (Gallagher et al, 1999;Nguyen et al, 2008). Several of the individuals analyzed were heterozygous at seven NOR-bearing chromosomes, four of which were homoplasic in the reconstructed tree.…”
Section: Consequences For Phylogenetic Reconstructionsmentioning
confidence: 99%
“…The vast majority of these investigations are based on the silverstaining method which presents two drawbacks: it reveals only the active fraction of the rRNA genes, that is, those that were transcribed during the previous interphase, and in some cases, it may lead to nonspecific staining of heterochromatic regions (Dobigny et al, 2003;Cabrero and Camacho, 2008;Carvalho et al, 2009). Access to the genes themselves by the fluorescence in situ hybridization (FISH) technique has provided a cytogenetic tool to explore the extent of NOR diversity between species irrespective of their expression status (Matsubara et al, 2004;Datson and Murray, 2006;Nguyen et al, 2008). However, many of these studies involve comparisons between species, and thus provide little information on the evolutionary processes acting on variation at the intraspecific level.…”
Section: Introductionmentioning
confidence: 99%